MASS PRODUCTION OF ENTOMOPATHOGENIC FUNGI USING AGRICULTURAL PRODUCTS - BHANU PRATAP BHADAURIA; SMITA PURI; P. K. SINGH (The Bioscan, 2012)
The success of microbial control of insect pests depends not only on the isolation, characterisation and pathogenicity, but also on the successful mass production of the microbial agents in the laboratory. Large-scale availability of the pathogen is a primary requirement in the biocontrol programme. Beauveria bassiana is an entomopathogenic fungus which is used against a number of insect pests. To develop an efficient method for the utilization of this fungus as a bio control agent, various grains and liquid media such as Potato Dextrose Broth and Sabouraud’s Dextrose Broth were screened. Pea amended media produced maximum biomass of the test fungus while SDB produced significantly higher spore production of the fungi. Highest conidial count (9.06 × 107 conidia mL-1) was observed on cowpea media followed by soybean.